2022
DOI: 10.1186/s12877-022-03491-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of skeletal muscle mass by aspartate aminotransferase / alanine aminotransferase ratio, insulin and FSH in Chinese women with sarcopenia

Abstract: Background: Sarcopenia is an age-related skeletal muscle disorder that involves a loss of muscle mass or strength and physiological function. Skeletal muscle deteriorates in both quantity and quality. The endocrine system is an important regulator of muscle metabolism. Therefore, we aimed to explore the relationship between biochemical markers and muscle mass in sarcopenia. Methods: We used the AWGS 2014 as the diagnostic criteria for sarcopenia, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…In the study conducted by Merchant RA and colleagues, it was indicated that a lower BMI is associated with a higher risk of developing sarcopenia [ 18 ]. A previous study conducted on a Chinese female population aged over 50 also indicated that individuals with low muscle mass had lower BMI,ALT levels, consistent with our findings [ 19 ]. In a longitudinal cross-sectional study spanning three years in China, it was indicated that there is an association between fasting plasma C-peptide levels and the likelihood of sarcopenia [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study conducted by Merchant RA and colleagues, it was indicated that a lower BMI is associated with a higher risk of developing sarcopenia [ 18 ]. A previous study conducted on a Chinese female population aged over 50 also indicated that individuals with low muscle mass had lower BMI,ALT levels, consistent with our findings [ 19 ]. In a longitudinal cross-sectional study spanning three years in China, it was indicated that there is an association between fasting plasma C-peptide levels and the likelihood of sarcopenia [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, patients with sarcopenia exhibited lower insulin levels [10,19]. In our study, considering the potential impact of insulin therapy on insulin levels, we innovatively utilized C-peptide as a research parameter, circumventing the influence of medication.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted on a Chinese female population aged over 50 also indicated that individuals with low muscle mass had lower BMI,ALT levels, consistent with our ndings. [20] Meanwhile, we posit that muscle mass is associated with pancreatic beta-cell secretion function .Compared with those without low muscle mass, those with low muscle mass had signi cantly higher female, Ever/current smoking, Ever/current drinking, FPG(P < 0.01), HbA1c(P < 0.05), and GA(P < 0.05) concentration (P < 0.001 for gender; P = 0.013 for Ever/current smoking; P = 0.005 for Ever/current drinking; P < 0.01 for FPG; P < 0.01 for HbA1c, GA). Some studies indicate a higher prevalence of sarcopenia in elderly male patients with type 2 diabetes mellitus (T2DM), [21,22] consistent with the ndings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, insulin levels in both the sarcopenia and nonsarcopenia groups were correlated with muscle mass. [20]In our study, considering the potential impact of insulin therapy on insulin levels, we innovatively utilized C-peptide as a research parameter, circumventing the in uence of medication. Our study also indicates lower C-peptide levels in patients with low muscle mass in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines released by adipose tissue produce important modifications during aging and can affect muscle metabolism and physiology. Therewithal, catabolic hormones such as cortisol and angiotensin II can accelerate age-induced muscle atrophy as they are involved in muscle wasting, and their levels increase with age [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%